How to draw cartoon reptiles - Visca, Curt; Visca, Kelley (New York : PowerKids Press, 2003)
Provides facts about different kinds of reptiles, as well as step-by-step instructions for drawing cartoons of each one.
Includes index.
4 - 9 years
Keywords: Cartooning -- Technique; Reptiles -- Caricatures and cartoons; Reptiles in art